Deep Learning-Based Local Literature Instruction and Cultural Identity Development in Higher Education: A Literature Review - Sri Meiti Anggraini Ahaya; Harto S. Malik (FOSTER: Journal of English Language Teaching, 2026)
Local literature learning plays an important role in higher education by supporting the preservation of cultural values and the development of students’ cultural identity. When implemented through a deep learning approach, literature education can foster meaningful understanding, critical reflection, and culturally grounded learning experiences. Accordingly, this study aims to examine (1) the contribution of local or regional literature education to students’ cultural identity development in higher education; (2) the pedagogical applications of deep learning approaches in literature and cultural studies; and (3) how the integration of local literature and deep learning enhances students’ cultural awareness and social sensitivity. This study employs a systematic literature review design by analyzing 19 peer-reviewed journal articles published within the last ten years. The findings indicate that local literature functions as a culturally contextualized knowledge system that transmits traditional values and social meanings, thereby strengthening students’ cultural identity and sense of belonging. Deep learning pedagogy encourages higher-order thinking, reflective engagement, and contextual interpretation of literary texts. Furthermore, the integration of local literature and deep learning enhances students’ cultural awareness, empathy, and social sensitivity. In conclusion, integrating local literature learning with deep learning pedagogy offers a culturally responsive approach to literature education in higher education.